PENGEMBANGAN E-BOOK BERBASIS FLIP PDF PROFESSIONAL PADA MATERI KERAGAMAN RUMAH ADAT INDONESIA KELAS IV SEKOLAH DASAR - Widiyawati; Sukardi; Aldora Pratama (STKIP Subang, 2023)
The lack of availability of learning media and the lack of use of technology in learning make the millennial generation forget cultural values and rarely preserve traditional Indonesian culture, one of which is traditional houses in Indonesia.The purpose of this study is to produce a product in the form of a Flip PDF Professional based E-Book on the diversity of valid and practical Indonesian traditional houses. This type of research and development uses (Research and Development) using the ADDIE model which consists of 5 stages, namely, 1) Analyze 2) Design, 3) Development, 4) Implementation, 5) Evaluation). The subjects in this study were 1 media expert validator, 1 material expert validator, 1 linguist validator, and 3 elementary school grade IV students and 8 small group students. Data collection instruments include media validation sheets by validators, practical questionnaire sheets from students and documentation. Based on the results of the research, an average assessment by media experts was obtained by 80%; material experts by 96% linguists by 91% with valid categories, and the results of student response questionnaires were one to one by 81.33% and small group field tests by 90.5% with practical categories. Keywoard: E-Book, Flip PDF Professional